Bioprospection of plant extracts from the Caatinga for the control of Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae) - Sá, Daniele Alves de; Silva, Juliane Nogueira da; Silva, Maria Amélia de Oliveira; Souza, Almir Rogerio Evangelista de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The objective was to evaluate the insecticidal effect of extracts of Ziziphus joazeiro Mart., Croton sonderianus and Amburana cearenses on the hatchability of eggs of the fall armyworm Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae). The extracts of the three plant species were produced at concentrations of 5%, 10% and 15%, and distilled water as a control. For each concentration, paper towel discs containing 30 eggs were immersed for 30 seconds and then left to dry, being placed in plastic pots. Each treatment consisted of four replicates containing 30 eggs each. After 24 hours of exposure to the extracts, daily readings were taken for eight days, considering that eggs not hatched after this period were not viable. During the analysis of the ovicidal effect of plant extracts on the embryonic development of S. frugiperda eggs, the hatching rate and efficiency rate of the extracts were verified. We can conclude that the hydroalcoholic extracts of C. sonderianus, Z. joazeiro and A. cearenses were efficient in inhibiting the hatchability of S. frugiperda larvae at doses of 10 and 15% of the plant structures, proving that the extracts of these plant species can be used in the reduced hatchability of eggs.